(untitled) (JURNAL KEPERAWATAN, 2025)
Background: Hypertension is a non-communicable disease that can cause serious complications such as stroke, kidney failure, and heart disease. Non-pharmacological therapies such as soaking feet in warm water with a mixture of Epsom salts can be used in lowering blood pressure. This study aims to determine the application of soaking feet in warm water with Epsom salts in lowering blood pressure in hypertensive patients in the work area. The purpose of this study is to determine blood pressure changes with the application of warm water soaking foot therapy with a mixture of epsom salt in hypertensive patients. This research method uses a descriptive method with a case study approach. The data collection technique used a Small Comparative Study with a sample of 2 people. Sample determination was carried out using a non-probability sampling technique. The sample consisted of 2 respondents who suffered from 1st degree hypertension. Results There was a significant difference in average blood pressure before and after the application of warm water foot soaking therapy with a mixture of Epsom salts. Subject’s blood pressure before being given therapy on the first day was 146/96 mmHg and after being given the intervention for 7 days the subject’s blood pressure dropped to 128/84 mmHg, in subject 2 the directional pressure before being given therapy on the first day was 156/96 mmHg and after being given the intervention for 7 consecutive days the subject’s blood pressure dropped to 134/90 mmHg